Organocatalytic Enantioselective Construction of Axially Chiral Tetrasubstituted Allenes via 1, 6‐Addition of Alkynyl Indole Imine Methides with 2‐Substituted Indoles. Issue 3 (16th December 2021) - Wu, Yu; Yue, Zhibin; Qian, Chenxiao; Chen, Xuling; Li, Fushuai; Li, Pengfei; Li, Wenjun
Abstract: An organocatalytic construction of axially chiral tetrasubstituted allenes featuring indole skeletons has been established. With the aid of chiral phosphoric acid, alkynyl indole imine methides were formed in situ from α‐(3‐indolyl) propargylic alcohols, followed by the asymmetric 1, 6‐conjugate addition with 2‐substituted indoles, furnishing axially chiral indole‐containing tetrasubstituted allenes in generally high yields and enantioselectivities. Abstract : An organocatalytic construction of axially chiral tetrasubstituted allenes featuring indole skeletons has been established. With the aid of chiral phosphoric acid, alkynyl indole imine methides were formed in situ from α‐(3‐indolyl) propargylic alcohols, followed by the asymmetric 1, 6‐conjugate addition with 2‐substituted indoles, furnishing axially chiral indole‐containing tetrasubstituted allenes in generally high yields and enantioselectivities.